Workshop on a Collaborative Platform for Agricultural Research in Sub-Saharan Africa, WARDA, Bouaké, 14 to 16 March 2001, Workshop Report - International Service for National Agricultural Research; West Africa Rice Development Association (International Service for National Agricultural Research, 2001)
The main objective of the workshop on a collaborative platform for agricultural research in Sub-Saharan Africa was to develop a framework for producing more productive partnerships that will maximize the advantages and efficiency gains of collaboration. Participants represented the CGIAR (WARDA and ISNAR), the African Association of Universities, and the academic community from 12 countries in Eastern, Western, Central and Southern Africa. In developing a successful partnership, collaborating partners must have a shared vision, goals, objectives (strategic and specific), values, and principles underlying the partnership; must clearly see the advantages of collaborative partnership; and partners must demonstrate genuine appreciation of their respective constraints. During the workshop it was recognized that the original concept of a collaborative platform involving only the CGIAR centers and the universities was too narrow and, therefore, other partners need to be involved. The workshop endorsed a draft collaborative platform covering vision, goal, objectives, and follow-up program of work. Elements of the implementation process to include development of collaborative agreements of partnership among participating institutions and the establishment of monitoring and evaluation mechanisms for partnerships were agreed upon. Others are the establishment of steering committees to monitor progress of the implementation of partnership programs, expected output, impact, and dissemination of information on programs of collaborative platforms